Scientometrics analysis of the academic activities of the Azerbaijan State University of Culture and Arts in 2021-2023 (Some specific features of the activity) - Aliyeva, Sadagat Agasafar; Kazimi, Parviz Firudin Oqlu (Technium Social Sciences Journal, 2022)
On the one hand, activities in various areas of culture and art, research work, on the other hand, the collection and involvement of creativity and performing arts in education are based on historical traditions. In such activities, it is important to balance dominance and determine the average limit. As important as the scientific analysis of the creative activity of performers is, it is just as important to develop scientific research, to study and evaluate world cultural processes, on the one hand, and to carry out a scientific presentation of national and local cultural products. Therefore, the classification of research works in the field of culture and art at three levels, the evaluation of scientific materials at the local, regional and global levels, allows us to obtain rational results. To this end, we have focused on the research work of the Azerbaijan State University of Culture and Arts over the past three years, the statistics of scientific articles of our scientists and the activities of scientific journals of our university. The prospects of the work done in the direction of expanding scientific activity at our university are also analyzed.